2020
DOI: 10.1183/23120541.00232-2019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of pulmonary artery dimensions measured on high-resolution computed tomography scan for identifying pulmonary hypertension

Abstract: BackgroundOn high-resolution computed tomography (HRCT), pulmonary artery (PA) dimensions may hint at the presence of pulmonary hypertension. We aimed to determine how accurately various measures of the PA, as viewed on HRCT, predict right heart catheterisation (RHC)-confirmed pulmonary hypertension.MethodsWe retrospectively reviewed patients who had HRCT and RHC between 2010 and 2018. Analyses considered respiratory cycle, pulmonary hypertension diagnostic criteria, time between HRCT and RHC, and subgroup ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Our results did not change even when we assessed the correlation between PA-Ao ratio and mPAP in LAM and PLCH isolatedly (data not shown). We found that 0.86 was the cut-off with the highest accuracy for predicting PH, which was quite similar to that obtained in investigations with patients with IPF and COPD [36,37] . The lack of difference in pulmonary function parameters between patients with PA-Ao ratio > 1 and those with PA-Ao ratio ≤ 1 suggests that other mechanisms in addition to parenchymal involvement and hypoxic vasoconstriction, such as pulmonary vascular involvement and cardiac dysfunction, may have contributed to the enlargement of PA-Ao ratio in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Our results did not change even when we assessed the correlation between PA-Ao ratio and mPAP in LAM and PLCH isolatedly (data not shown). We found that 0.86 was the cut-off with the highest accuracy for predicting PH, which was quite similar to that obtained in investigations with patients with IPF and COPD [36,37] . The lack of difference in pulmonary function parameters between patients with PA-Ao ratio > 1 and those with PA-Ao ratio ≤ 1 suggests that other mechanisms in addition to parenchymal involvement and hypoxic vasoconstriction, such as pulmonary vascular involvement and cardiac dysfunction, may have contributed to the enlargement of PA-Ao ratio in our study.…”
Section: Discussionsupporting
confidence: 89%
“…This is the first study to identify an increased PA diameter, as assessed by CT, as an independent predictor of both myocardial injury and mortality in COVID-19 patients. PA diameter has been shown to correlate with the presence of pulmonary hypertension 16 and has been associated with increased mortality in patients with chronic obstructive pulmonary disease. 17 COVID-19 pneumonia is characterized by a systemic inflammatory disorder with a hypercoagulation state, endothelial dysfunction, hypoxic vasoconstriction leading to a hypoxia-inducible transcription factor-dependent signalling pathway, that may predispose to acute endothelial damage of the pulmonary circulation, the occurrence of thrombo-embolic phenomena, and/or small vessel thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…After eliminating of duplicates and reading of the titles/abstracts, we agreed on 36 articles meeting inclusive criteria to further browse the full text. Ultimately, nine retrospective studies 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 were taken into our review for further meta‐analysis (Figure 1 ), including 1238 COPD participants, of whom 548 patients were diagnosed as COPD‐PH. The patients with COPD‐PH in five studies were definite diagnosed according to RHC and the cut‐off value of CT‐based PA: A ratio was greater than or equal to one in six research (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%